Insights into the airborne microorganisms in a Sichuan south-road dark tea pile fermentation plant during production - Liu, Miaoyi; Li, Xian; Li, Yimiao; Zou, Yao (Frontiers in Microbiology, 2024)
Sichuan south-road dark tea (SSDT) is generally produced by fixing, rolling, pile fermentation, and drying, with microbial action in pile fermentation as the key factor affecting tea quality formation. The air of the SSDT pile fermentation plant (SSDTPP) is considered an important microbial source, but its research is limited. Here, SSDTPP air was collected on the 1st (SSDT1), 12th (SSDT2), and 24th (SSDT3) days of pile fermentation, and high-throughput sequencing revealed 2 and 24 phyla, 9 and 49 classes, 18 and 88 orders, 28 and 153 families, 38 and 253 genera, and 47 and 90 species of fungi and bacteria, respectively, in all samples. SSDT1 and SSDT2 individually had the highest fungal and bacterial diversity, while Aspergillus was dominant throughout the pile fermentation with an abundance of 34.6%, 91.17%, and 67.86% in SSDT1, SSDT2, and SSDT3, respectively. Microbial populations in SSDT1 were mainly dominant in xenobiotics biodegradation and metabolism, amino acid metabolism, biosynthesis of other secondary metabolites, etc., but more human disease-related functions were found in SSDT2. SSDT3 mainly focused on the metabolism of other amino acids, carbohydrate metabolism, etc. Additionally, 104 genera and 22 species coexisted in SSDTPP air and piled SSDT, frequent microbial exchange may occur between them. The results pave the way for microbial traceability of piled SSDT during production and functional microbial research.